Quality control and improvement techniques difabel corner of UIN sunan kalijaga yogyakarta - Arif Prasetyo; Roihan Sadad; Abidin Latua (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Difabel Corner UIN Sunan Kalijaga Yogyakarta is one of the inclusive service centers committed to providing optimal accessibility and support for students with disabilities in the university environment. This research aims to examine the application of quality control and quality improvement techniques in the management of Difabel Corner services. This research uses a literature study approach and descriptive analysis to explore quality management concepts from figures such as Deming, Juran, Crosby, Ishikawa, as well as international standards such as ISO 9000, and their relevance in educational services for students with disabilities. The results showed that the implementation of supervisory techniques such as service monitoring, periodic evaluation, service standardization, as well as quality improvement through human resource development, utilization of adaptive technology, external collaboration, and continuous audit can increase the effectiveness of Difabel Corner services. The implementation of these strategies not only ensures compliance with inclusivity standards, but also strengthens the capacity of the service in responding to the needs of students with disabilities in a sustainable manner. This article contributes to offering an implementation framework for monitoring and improving the quality of inclusive education services in higher education.